The Role of Organizational Factors in Enabling, and of Autonomy in Potentializing Intrapreneurial Behavior: Mechanisms and Preconditions - Alex de Souza Santana; Cristina Dai Prá Martens; Flávio Santino Bizarrias; Mauro Luiz Martens (BAR: Brazilian Administration Review)
Objective: the study explores the complex interaction between intrapreneurial behavior, organizational factors, and individual characteristics, with a focus on a moderated-mediation model. This model incorporates individual autonomy as a key enhancer and considers organizational elements like time availability, managerial support, rewards, and structure as mediating factors. Methods: data were collected through a survey of various companies, and the analysis utilized multivariate statistical methods for analyzing multiple relationships between variables, the PROCESS© macro for mediated moderation, and a complementary approach to find essential factors for an outcome, identifying the critical levels of each construct for promoting intrapreneurial actions. Results: the results demonstrate that organizational factors and autonomy conditionally influence intrapreneurship, establishing essential thresholds for these effects. This study contributes to the intrapreneurship discourse by offering a theoretical framework that integrates both individual and organizational dynamics. It employs a novel mediated-moderation approach to explore their combined impact on intrapreneurial behavior and innovates by identifying the necessary conditions for fostering intrapreneurial activities within this framework. Conclusions: the study concludes that practitioners should focus on enhancing autonomy to maximize the potential contributions of intrapreneurial individuals while also managing organizational factors that create a supportive environment. It provides specific levels of these factors for effective management, offering a comprehensive understanding of how personal and corporate dynamics interact to promote intrapreneurial behavior.